IMPLEMENTASI PENGALOKASIAN DANA PAJAK (EARMARKING TAX) DARI PENERIMAAN PAJAK ROKOK TERHADAP UPAYA KESEHATAN MASYARAKAT DI PROVINSI SULAWESI UTARA - Tambing, Damayanti Rante; Saerang, David; Wokas, Heince (Universitas Sam Ratulangi, 2017)
The cigarette tax is applied in the province of North Sulawesi in 2014. Cigarette tax is a regulate tax that is specific to the health, then the purpose of applying cigarette tax is to protect the public against the dangers of cigarettes. Therefore, cigarette tax in earmarking tax policy is allocated at least 50% for public health service. The purpose of this study is to analyze the implementation of earmarking tax of Cigarettes tax to public health services in North Sulawesi Province has been in accordance with applicable legislation. The method used is descriptive qualitative. The results of this study can be seen that for the year 2016, earmarking tax policy of tobacco tax has not been applied in accordance with the appropriate. This is because spending on public health efforts has not reached the minimum value of 50% of tax revenues for provinces. Earmarking tax in North Sulawesi province runs with revenue and expenditure budget system (APBD), which is implemented through the regional public treasury account (RKUD) in terms of income and expenditure. Dinas Kesehatan as an agency that budgeted for public health effort would improve public health service standard by maximizing spending for the designation. Agencies related to the cigarette tax budgeting policy would prescribe standard operating procedures so that control over these policies can be done as appropriateKeywords: Earmarking tax policy, cigarette tax